Pregnant patient with extranodal CNS Rosai-Dorfman disease with new-onset seizures: the conundrum of differentiating disease progression from eclampsia. Issue 2 (18th February 2021) - Swor, Katie; Zutshi, Deepti; Dubey, Elizabeth; Gonik, Bernard
Abstract : A 31-year-old woman at 30 weeks gestation presented to the emergency department following multiple seizures. Her history was significant for extranodal Rosai-Dorfman Disease (RDD) with central nervous system (CNS) lesions. RDD, a rare form of non-Langerhans cell histiocytosis, commonly presents with non-tender cervical lymphadenopathy. CNS involvement accounts for a small number of cases in those with extranodal disease. Patients with CNS RDD can have a variety of neurological symptoms, including seizures. Eclampsia, a relatively rare obstetric hypertensive disorder, is always within the differential diagnosis for patients presenting with late gestation seizures. We present the challenging evaluation and treatment of a patient whose clinical picture did not clearly differentiate eclampsia from new onset seizures related to progression of her RDD. This conundrum perhaps resulted in unnecessary preterm operative delivery of a critically ill patient. Only follow-up of the patient helped clarify the likely antepartum diagnosis.